2011
DOI: 10.1074/jbc.m111.255489
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 14-3-3 Proteins in the Second Epidermal Growth Factor-induced Wave of Rac1 Activation in the Process of Cell Migration

Abstract: Background:The spatiotemporal regulation of Rac1 controls cell migration. Results: EGF induced two waves of Rac1 activation in the process of cell migration. Conclusion: 14-3-3 proteins regulate the second EGF-induced wave of Rac1 activation by interacting with RacGEF. Significance: The second wave of Rac1 activation might be required for EGF-induced cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…This is consistent with the previous reports showing that 14-3-3 binding to Tiam1 is required for Rac1 activation. 44,45 A previous study found S60A mutation was stabilized but with reduced interaction with 14-3-3, while other single mutations (S172 or S231) have no effect on the half-life of Tiam1. 32 It was hypothesized that 14-3-3 binding to different combination of phosphorylation sites resulted in distinct conformational changes, thereby regulating Tiam1 stability.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with the previous reports showing that 14-3-3 binding to Tiam1 is required for Rac1 activation. 44,45 A previous study found S60A mutation was stabilized but with reduced interaction with 14-3-3, while other single mutations (S172 or S231) have no effect on the half-life of Tiam1. 32 It was hypothesized that 14-3-3 binding to different combination of phosphorylation sites resulted in distinct conformational changes, thereby regulating Tiam1 stability.…”
Section: Discussionmentioning
confidence: 96%
“…Rac1-GTP pull-down assay was carried out as described previously. (6) Leukotriene C 4 measurement. A431 cells were pretreated with or without drugs for 15 min and then stimulated with 30 ng ⁄ mL EGF.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that epidermal growth factor (EGF) induces biphasic lamellipodia formation, which was observed at 5 min and 12 h, in the process of cell migration of human epidermoid carcinoma A431 cells and human thyroid carcinoma TT cells. These two waves of lamellipodia formation were reflected by two waves of EGF‐induced Rac1 activation, which were observed at 2–5 min and 6–12 h, respectively . The biphasic timing of Rac1 activation mirrors the biphasic formation of lamellipodia.…”
mentioning
confidence: 94%
“…Based on a chemical genomic-based pathway analysis for EGF-mediated signaling in various migrating cancer cells, we reported that common and cell-type specific pathways existed during EGF-induced cell migration [15,16]. Moreover, we revealed that the 5-lipoxygenase/leukotriene receptor 1/cysteinyl leukotriene receptor 1 signaling pathway-mediated Tiam1 expression is involved in EGF-induced cell migration in A431 cells [17,18]. Through further investigation into the mechanism by which EGF induces cell migration, we found that EGF decreased E-cadherin expression in colorectal carcinoma LoVo cells.…”
Section: Introductionmentioning
confidence: 90%